MERTK mediated novel site Akt phosphorylation alleviates SAV1 suppression - Yao Jiang (Nature Portfolio, 2019)
Hyperactivation of Akt promotes tumorigenesis. Here, the authors show that SAV1, a member of Hippo signalling, interacts with Akt to suppress Akt activity and MERTK-mediated Akt phosphorylation relieves this suppression to facilitate Akt oncogenic activity in clear cell renal carcinomas.